Exploratory geochemical assessment of stream water and sediment contamination in Gatumba tin and tantalum mining district, Rwanda. - Flügge, Judith; Muwanga, Andrew; Trümper, Kerstin; Zachmann, Dieter; Pohl, Walter (My University, 2009)
Stream waters are not contaminated with dangerous inorganic elements. According to WHO guidelines, these waters are acceptable for lifelong consumption without risk to health. Note, however, that microbial waterborne disease vectors were not investigated. Stream sediments generally have relatively low contents of most elements that may be derived from pegmatites. Of mine-related contaminants, only uranium and arsenic exceed their respective average crustal abundance. Both appear to be higher near former mine sites but this is probably not caused by mining. Causes are rather primary hydrothermal and secondary supergene dispersion, and recent mobilisation because of intensive agricultural use. Yet at present, the welfare of the local population is not threatened. The most serious hazard is human interference with groundwater by abstracting drinking water either from wells in valley fill or from deeper horizons of the regolith. Overall, our work suggests that past mining at Gatumba caused little dispersion of deleterious elements.